Research on Innovative Application Path of Sustainable Materials in Contemporary Jewelry Design - Li, Ruisi; Yu, Yang (Studies in Social Science & Humanities, 2025)
Taking sustainable development as the constraint and motivation, this paper mainly discusses the performance characteristics, advantages and limitations of recycled metal, natural materials and waste materials in jewelry design, and takes international brands (Cartier and Chopin) and domestic practices (bamboo and wood, broken porcelain and comprehensive recycling) as samples to sort out the systematic strategy of material-technology-design-market. The research shows that sustainable materials not only significantly reduce the environmental load, expand the aesthetic vocabulary of contemporary jewelry, but also enhance brand value and social recognition through supply chain governance and narrative construction; However, its large-scale promotion is still limited by processing technology, consumer mentality and industry standards. Some strategies are put forward, such as process integration of new materials and old technologies/old materials and new technologies, green design language and traceability logo system, and closed-loop mechanism of brand education and recycling for Z generation, which provide executable reference for the green transformation of the jewelry industry.